Policy Evaluation of TPS3R Waste Management in Durungbedug Village: Evaluasi Kebijakan Pengelolaan Sampah TPS3R di Desa Durungbedug - Salima, Nabila; Rodiyah, Isnaini (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Waste accumulation remains a significant environmental challenge in Indonesia, especially at the local level. Specific Background: The Durungbedug Village government established a Reduce, Reuse, Recycle Waste Processing Site (TPS3R) to improve community-based waste management. Knowledge Gap: However, the effectiveness and efficiency of this program have not been comprehensively evaluated. Aims: This study aims to assess the waste management policy implementation in TPS3R Durungbedug Village using William Dunn’s six evaluation indicators. Results: The findings show that TPS3R has improved environmental cleanliness and reduced open waste disposal. Nevertheless, challenges persist, such as irregular waste collection, limited labor, and uneven community participation. Novelty: This study highlights how local policy implementation shapes public environmental behavior at the micro level. Implications: The results provide insights for strengthening sustainable waste management policies through participatory and structured evaluation mechanisms. Highlights: Local waste policy evaluation using Dunn’s framework Community participation and operational efficiency Policy improvement for sustainable waste management Keywords: Policy Evaluation, Waste Management, TPS3R, Community Participation, Sustainability